THE PRAGMATICS OF POLITENESS: ANALYZING ‘FACE’ AND INDIRECTNESS IN MODERN ENGLISH DISCOURSE - Umaraliyev Mukhriddin, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
This  article  analyzes  the  sociolinguistic  constructs  of  politeness  within  the English language. By applying the "Politeness Theory" of Brown and Levinson, the paper explores how speakers use linguistic strategies to mitigate "Face-Threatening Acts"  (FTAs).  The  study  examines  the  distinction  between  positive  and  negative politeness  and  its  implications  for  cross-cultural  communication  in  an  English-speaking context.